Genetic Variants in HSD17B3, SMAD3, and IPO11 Impact Circulating Lipids in Response to Fenofibrate in Individuals With Type 2 Diabetes. Issue 4 (3rd November 2017) - Rotroff, Daniel M.; Pijut, Sonja S.; Marvel, Skylar W.; Jack, John R.; Havener, Tammy M.; Pujol, Aurora; Schluter, Agatha; Graf, Gregory A.; Ginsberg, Henry N.; Shah, Hetal S.; Gao, He; Morieri, Mario‐Luca; et al.
Abstract : Individuals with type 2 diabetes (T2D) and dyslipidemia are at an increased risk of cardiovascular disease. Fibrates are a class of drugs prescribed to treat dyslipidemia, but variation in response has been observed. To evaluate common and rare genetic variants that impact lipid responses to fenofibrate in statin‐treated patients with T2D, we examined lipid changes in response to fenofibrate therapy using a genomewide association study (GWAS). Associations were followed‐up using gene expression studies in mice. Common variants in SMAD3 and IPO11 were marginally associated with lipid changes in black subjects ( P < 5 × 10 ‐6 ). Rare variant and gene expression changes were assessed using a false discovery rate approach. AKR7A3 and HSD17B13 were associated with lipid changes in white subjects ( q < 0.2). Mice fed fenofibrate displayed reductions in Hsd17b13 gene expression ( q < 0.1). Associations of variants in SMAD3, IPO11, and HSD17B13, with gene expression changes in mice indicate that transforming growth factor‐beta (TGF‐β) and NRF2 signaling pathways may influence fenofibrate effects on dyslipidemia in patients with T2D.